(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This growing interest of the international scientific specialized commissions is due to the role that the audit committee can play, as one of companies’ governance tools, to increase the accuracy and transparency of the financial information disclosed by the companies, through its oversight role on the process of preparing financial reports, its supervision on the internal audit function within the companies, and supporting its independency, as well as coordinating the efforts between the internal control unites and the external auditor represented by the (Board of Supreme Audit) to clear the observations and irregularities in order to reduce the fraud cases. This research was built on an applied sample of audit committee works in the public sector (state institutions) in Iraq which lacks of such committees; that form part of the governance tools, and those institutions are hit by various types of fraud and a rampant corruption is dominating their entire facilities, moreover, the Board of Supreme Audit plays a significant role in detecting the financial irregularities, cases of fraud and financial manipulation within the state institutions, pursuant its law 31 (2011).